Requirements and perspectives of development of quality of diesel fuels used for exploitation especially in urban traffic considering environmental protection - Biernat, Krzysztof (Studia Ecologiae et Bioethicae, 2004)
Combustion of liquid fuels including diesel fuels is one of the major processes influencing the condition of the environment. Requirements for the quality of diesel fuels are related to the development of the construction of fuel feed systems, combustion and exhaust gas systems, and also with growing expectations from environmental protection. In the article are shown basic connections between standards of diesel fuels used in urban traffic described by proper norms and exploitation overworks and environmental expectations. Developmental tendencies of the quality of those fuels are also mentioned.